Time Course of Biochemical and Metabolic Parameters During and After COVID-19 - Ghoreshi, Zohreh-al-sadat; Abbasi-jorjandi, Mojtaba; Asadikaram, Gholamreza; Sharif-zak, Mohsen; Haddad, Mohammad Khaksari; Afgar, Ali; Arefinia, Nasir; Dabiri, Shahriar; Rosen, Clifford (Current Medicinal Chemistry, 2025)
BackgroundLong COVID is characterized by the persistence of symptoms among individuals who are infected with the SARS-CoV-2 virus. The enduring impact of these long-term effects on the health and well-being of those affected cannot be denied.Methods470 patients with SARS-CoV-2 were consecutively recruited in this longitudinal study. The participants were entered into moderate, severe, and critical groups. 235 out of 470 participants were female. The levels of fasting blood sugar (FBS), alanine transaminase (SGPT), aspartate aminotransferase (SGOT), alkaline phosphatase (ALP), creatinine (Cr), urea, uric acid (UA), and total protein (TP) were measured during hospitalization and again at one and three months after infection. The levels of Zn and hemoglobin A1c (HbA1c) were also measured only during hospitalization.ResultsCOVID-19 severity was associated with high levels of glucose, urea, Cr, ALT, AST, ALP, and HbA1c, and low levels of Zn, UA, and TP. There were significant sex differences for these markers at all three-time points. Glucose, urea, Cr, ALT, AST, and ALP all decreased three months after infection, whereas the levels of UA and TP returned towards normal.ConclusionCOVID-19 infection affects the levels of multiple biochemical factors in a gender-dependent manner. The biochemical changes become more tangible with increasing disease severity, and several of these predict mortality. Levels begin to return to normal after the acute phase of the disease, but in some individuals, at three months, several markers were still not within the normal range. Whether the trajectory of these changes can predict long COVID requires further testing.
Keywords: COVID-19